1997
DOI: 10.1097/00000478-199711000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Abnormalities and Clonal Evolution in an Adult Hepatoblastoma

Abstract: Hepatoblastomas usually occur in children < 3 years of age, and only occasional adult cases have been described. To date, 20 cytogenetically abnormal childhood hepatoblastomas have been reported. Karyotypic investigations have shown that most hepatoblastomas are diploid or hyperdiploid, often displaying trisomies for chromosomes 2 and 20. We have cytogenetically investigated an adult hepatoblastoma for which no previous karyotypic data exist. A hypertriploid stemline with multiple numerical and structural chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…[8][9][10]32,33 Such cytogenetic features, however, are not confined to HCC and have been suggested in other solid tumors 26 such as hepatoblastoma, pancreatic, and colon cancers. [34][35][36] The involvement of the C-MYC oncogene in 8q and the putative tumor suppressor gene DLC-1 in 8p21-p22 has since been implicated in the pathogenesis of HCC. 37,38 However, in support of a previous cytogenetic report by Parada et al, 17 our finding of common breakpoints outside the centromeric region suggests that genes residing on the bands 8p1 and 8q1 also have a role in the development of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10]32,33 Such cytogenetic features, however, are not confined to HCC and have been suggested in other solid tumors 26 such as hepatoblastoma, pancreatic, and colon cancers. [34][35][36] The involvement of the C-MYC oncogene in 8q and the putative tumor suppressor gene DLC-1 in 8p21-p22 has since been implicated in the pathogenesis of HCC. 37,38 However, in support of a previous cytogenetic report by Parada et al, 17 our finding of common breakpoints outside the centromeric region suggests that genes residing on the bands 8p1 and 8q1 also have a role in the development of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of hepatic neoplasms in children are malignant, with hepatoblastoma (HBT) being the most common [2]. HBT characteristically develops in a noncirrhotic liver, tends to be solitary and localized to one liver lobe, is more common in boys, and almost always occurs before the age of 3 years, although occasional adult HBT have been reported [3][4][5]. Most cases are sporadic, but HBT have also been described in the context of a variety of syndromes and congenital malformations, such as hemihypertrophy, renal abnormalities, osteopetrosis, BeckwithWiedemann syndrome, precocious virilization in males, and familial adenomatous polyposis (FAP) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chromosome banding techniques, we used fluorescence in situ hybridization (FISH) to characterize further the identified 1q12-21 abnormalities in these cases and in one previously reported adult HBT [5].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive English literature search revealed only 36 reports including 40 patients with adult hepatoblastoma dating back to 1958 [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40]. Before Carter [9] initially reported a patient with adult hepatoblastoma in the English literature, hepatic embryonic mixed tumor, mixed tumor and embryonic tumor had been reported as hepatoblastoma [5,6,7,8,10].…”
Section: Resultsmentioning
confidence: 99%
“…Parada et al [26] cytogenetically investigated an adult patient with hepatoblastoma and found a genetic variation showing a hypertriploid stemline with multiple numerical and structural chromosomal aberrations. Weber et al [41] screened 34 hepatoblastoma tumors and 3 hepatoblastoma cell lines for DNA copy number changes.…”
Section: Discussionmentioning
confidence: 99%